Effects of Different Hypothermia on the Results of Cardiopulmonary Resuscitation in a Cardiac Arrest Rat Model. (4th April 2022) - Xu, Shaohua; Miao, Hui; Gong, Liming; Feng, Lijie; Hou, Xuliang; Zhou, Manhong; Shen, Hong; Chen, Wei
Abstract : Objective . To investigate the optimal temperature of hypothermia treatment in rats with cardiac arrest caused by ventricular fibrillation (VF) after the return of spontaneous circulation (ROSC). Methods . A total of forty-eight male Sprague-Dawley rats were induced by VF through the guidewire with a maximum of 5 mA current and untreated for 8 min. Cardiopulmonary resuscitation (CPR) was performed for 8 min followed by defibrillation (DF). Resuscitated rats were then randomized into the normothermia (37°C) group, milder (35°C) group, mild (33°C) group, or moderate (28°C) group. Hypothermia was immediately induced with surface cooling. The target temperature was maintained for 4 h before rewarming to 37 ± 0.5 ° C . Moreover, at the end of the 4 h, a rat in each group was randomly selected to be sacrificed for the cerebral cortex electron microscopy observation (n = 1 ). The other resuscitated animals were observed for up to 72 h after ROSC (n = 7 ). Left ventricular ejection fraction (LVEF) and left ventricular end diastolic volume (LVEDV) were measured. Survival time, survival rate, and neurological deficit score (NDS) were recorded for 72 h. Results . During hypothermia, higher LVEF was observed in the hypothermia groups when compared with normothermia group (35°C vs. 37°C, p < 0.05, 33°C and 28°C vs. 37°C, p < 0.01 ). Among the hypothermia groups, LVEF was higher in the 28°C group than that of 35°C (p < 0.05 ). However, both the heart rate (HR) (p < 0.01 ) and LVEDV (28°C vs. 35°C, p < 0.01, 28°C vs. 37°C and 33°C, p < 0.05 ) were lowest in the 28°C group when compared with the other groups. There were no significant differences of LVEF and LVEDV between the group 35°C and 33°C (p > 0.05 ). After rewarming, the LVEF of 35°C group was higher than that of group 37°C, 33°C, and 28°C (35°C vs. 37°C and 28°C, p < 0.01, 35°C vs. 33°C, p < 0.05 ). Group 35°C and 33°C resulted in longer survival (p < 0.01 ), higher survival rate (p < 0.01 ), and lower NDS (35°C vs. 37°C and 28°C, p < 0.01, 33°C vs. 37°C and 28°C, p < 0.05 ) compared with the group 37°C and 28°C. The extent of damage to cerebral cortex cells in group of 35°C and 33°C was lighter than that in group of 37°C and 28°C. The 35°C group spent less time in the process of cooling and rewarming than the group 33°C and 28°C (p < 0.01 ). Conclusions . An almost equal protective effect of milder hypothermia (35°C) and mild hypothermia (33°C) in cardiac arrest (CA) rats was achieved with more predominant effect than moderate hypothermia (28°C) and normothermia (37°C). More importantly, shorter time spent in cooling and rewarming was required in the 35°C group, indicating its potential clinical application. These findings support the possible use of milder hypothermia (35°C) as a therapeutic agent for postresuscitation.